A recuperação judicial da empresa em crise: hipóteses concretas de estímulo à sua preservação - Fernandes, Francisco Benedito (2018)
The present work deals with the Judicial Recovery of the Company, considering its legal aspects, as well as a reflection of its management regarding administrative controls in order to detect certain risks that can lead to a Judicial Recovery. It should not be forgotten that the effects of globalization, sustainability and social responsibility influence the competitive capacity of the company and are therefore indispensable elements for the exercise of its activity. In another area, the Brazilian economy is in a state of habitual stagnation, causing companies to go pale in their investments due to uncertainties of growth. Thus, Judicial Recovery in many cases is the remedy found for some companies that are financially compromised and still intend to remain in the market. Thus, Law 11,101 / 2005, appears as an antidote to facilitate this moment of crisis that companies go through, guaranteeing their restructuring in their activities, thus allowing them to achieve their social purpose. Judicial Recovery is a north to be achieved, so that jobs are maintained, as well as, national economic stability, since being in active activity can contribute to society in general. In this context, it is of the utmost importance for the company to make an X-ray of its economic and financial situation, to know if it is on the verge of bankruptcy risk and for that it is necessary the evaluation instruments that allow to understand the real situation of the company with respect to its Operations and their solvency. In this step, the purpose of the present study is to alert to the risk of discontinuity of the business business due to lack of adequate information for decision making. On the other hand, depending on the data obtained by the economic indexes, the path is Judicial Recovery. In the many more are the causes that lead a company to face a situation of risk, so much that economically speaking a company can be on the verge of an abyss when it has excess of billing or lack of billing, therefore, these must have the eyes turned of form Macro to a fiscal analysis, legal accounting in a more incisive way.